Biomimetic Solid‐State Nanochannels: From Fundamental Research to Practical Applications. Issue 21 (4th April 2016) - Xiao, Kai; Wen, Liping; Jiang, Lei
Abstract : In recent years, solid‐state smart nanopores/nanochannels for intelligent control of the transportation of ions and molecules as organisms have been extensively studied, because they hold great potential applications in molecular sieves, nanofluidics, energy conversion, and biosensors. To keep up with the fast development of this field, it is necessary to summarize the construction, characterization, and application of biomimetic smart nanopores/nanochannels. These can be classified into four sections: the fabrication of solid‐state nanopores/nanochannels, the functionalization methods and materials, the mechanism explanation about the ion rectification, and the practical applications. A brief conclusion and outlook for the biomimetic nanochannels is provided, highlighting those that could be developed and integrated into devices for use in tackling current and the future problems including resources, energy, environment, and health. Abstract : The development of the biomimetic smart nanopore/nanochannels is systematically summarized in four sections: the fabrication of solid‐state nanochannels/nanopores based on the materials, the functionalization methods and materials, the mechanism explanation, and the practical application.